Strontium Ranelate for the Treatment of Post-Menopausal Osteoporosis - Ismahan Bozbey,; Ayşe Peyman Yalçın, (Archives of Rheumatology, 2009)
Strontium ranelate is a new agent developed for the management of post-menopausal osteoporosis. It has dual action on bone metabolism in that it stimulates the formation of new bone tissue and decreases bone resorption. There are evidences that CaSR-dependent and -independent pathways mediate the beneficial effects of strontium ranelate. It was found that strontium ranelate reduces vertebral, nonvertebral and major nonvertebral fractures and it is well tolerated over 1, 3, 4, and 5 years in post-menopausal osteoporosis. A reduction in vertebral and nonvertebral fracture risk was also shown in senile osteoporosis, and it was well tolerated. It has been suggested that strontium ranelate is able to reduce the progression of spine osteoarthritis. Here, we review strontium ranelate's mechanism of action, results of efficacy and tolerability studies and its place in the management of post-menopausal osteoporosis. (Turk J Rheumatol 2009; 24: 149-55)